Size-dependent cyclic voltammetry study of silicon microwire anodes for lithium ion batteries. (1st November 2016) - Hansen, Sandra; Quiroga-González, Enrique; Carstensen, Jürgen; Föll, Helmut
Abstract: Silicon microwires as anodes for Li-ion batteries may show good cycling performance over 100 cycles as anodes for Lithium ion batteries without significant capacity losses. The life time of the anode, however, strongly depends on the way the battery is charged. Overcharging or undercharging may have severe negative consequences. This paper studies with the study of the operational voltage range of Si microwire anodes and its dependence on the dimensions of the wires. Cyclic voltammetry is used to identify the potentials for the different lithiation/delithiation events, while a modified cyclic voltammetry technique is used to study the dynamics of those processes. Specially prepared anodes with Si wires of different lengths and widths were used for the study.